FACTORS AFFECTING CAYENNE SUPPLY AT KOLAKA (THE STUDY IN RAYA MEKONGGA MARKET) - Haerunianti Haerunianti (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2016)
This study aims to determine the The Factors that Affect cayenne supply at Kolaka (The study in Raya Mekongga Market). Respondents were drawn at saturated sampling (census) of 43 respondents traders of cayenne. This research was conducted in Pasar Raya Mekongga District of Kolaka Kolaka, using descriptive analysis method. The results of the research that has been done with a model of multiple linear regression equation analysis using SPSS version 15, show that there is a relationship and a strong positive influence. That simultaneous with a significant level of 90% (a = 0.1) factors that affect the selling price of cayenne, chili price is great, the price curly chili, pepper and capital price effect on the number of deals in Pasar Raya cayenne Mekongga Kolaka. While partially with a significant level of 95% (a = 0.05) factors that affect the selling price of cayenne, chili great price, price cayenne and price of curls pepper significantly affect the amount of cayenne deals. While capital does not significantly affect the number of deals in Pasar Raya Mekongga Kolaka. In the coefficient of determination (R2) of 86.6% whereas the factors that influence the number of deals is explained by the variables included in the regression model, while the remaining 13.4% of the total deals cayenne influenced by other factors or variation of other variables that are beyond the regression model.